Inclusion of consumption into emissions trading systems: Legal design and practical administration - Roland Ismer; Manuel Haussner; Karsten Neuhoff; William Acworth (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
A world of unequal carbon prices requires measures aimed at preventing carbon leakage. Climate policy imperatives demand that such measures must be compatible with the goal of sending a carbon price signal down the value chain. For carbon intensive materials, the combination of dynamic free allocation combined with Inclusion of Consumption (IoC) into emissions trading systems such as the European Union Emissions Trading Scheme (EU ETS) arguably fulfils both the aims of preventing carbon leakage and of sending the price signal. The paper presents concrete proposals regarding the legal design and practical administration of this mechanism. It argues that the IoC is, provided appropriate choices are made, ripe for implementation.
Keywords: H23; K23; L61; 330; Carbon Pricing; value chain; consumption charge